Oxide dispersion strengthened steel and preparation method thereof

By stacking low-activated ferrite martensite and yttrium stacking for vacuum sealing, hot isostatic pressing and hot rolling treatment, and repeated stacking 3 to 10 times, the problems of diffusion strengthening, high cost and poor quality stability in ODS steel preparation were solved, and ODS steel preparation with high purity, controllable composition and controllable grains were achieved.

CN119614824APending Publication Date: 2025-03-14SOUTHWESTERN INST OF PHYSICS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411798472.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The preparation of ODS steel by smelting method cannot achieve true diffusion strengthening, large oxide size is difficult to remove, and insufficient rare earth oxides lead to failure to meet the performance standards; the mechanical alloying method has high production costs, low efficiency, and poor quality stability; the sol-gel method cannot be prepared in large quantities and the process is complex; additively manufactured ODS steel is prone to cracking, stress concentration and elemental segregation.

Method used

By processing low-activated ferrite martensite into strip steel, the surface treatment is vacuum sealed with yttrium stacking, hot isostatic pressing and hot rolling treatment, and repeated stacking 3 to 10 times to achieve oxide dispersion strengthening.

Benefits of technology

It realizes the rapid preparation of high-purity ODS steel, with controllable solid alloying components, controllable grains, and stable quality, avoiding the high cost and low efficiency of oxide floating in the smelting method and mechanical alloying method, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614824A_ABST
    Figure CN119614824A_ABST
Patent Text Reader

Abstract

The invention discloses oxide dispersion strengthened steel and a preparation method thereof, and relates to the technical field of ferrous metallurgy. The invention discloses a preparation method of oxide dispersion strengthened steel. The preparation method comprises the following steps: S1, processing low-activation ferrite martensite into strip-shaped steel; s2, the annealed steel is subjected to surface treatment; s3, the steel subjected to surface treatment and yttrium are stacked and subjected to wrapping treatment, and the wrapped steel is welded; s4, carrying out hot isostatic pressing treatment on the welded sheathed steel; and S5, after hot isostatic pressing, the sheathed steel is subjected to hot rolling treatment. The prepared oxide dispersion strengthened steel has the advantages of being high in purity, controllable in alloying component, controllable in crystal grain and stable in quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of iron and steel metallurgy, and in particular to oxide dispersion strengthened steel and a preparation method thereof. Background Art

[0002] Controlled nuclear fusion has become an international research hotspot as one of the fundamental ways to completely solve the energy problem. Since the first wall structural material must meet the harsh service environment, nano-oxide dispersion strengthened (Oxide Dispersion Strengthened ODS) steel has become the preferred structural material for the cladding due to its excellent radiation resistance and high-temperature creep strength. The oxide is generally a rare earth oxide, such as yttrium oxide. On the one hand, the excellent radiation resistance of ODS steel comes from the effective capture of radiation defects by the interface formed between a large number of ultrafine dispersed particles and the matrix. For example, the capture of helium bubbles generated by neutron irradiation can significantly improve the radiation swelling problem of the material; on the other hand, the pinning effect of nano-oxide particles or clusters with good high-temperature stability on dislocations and grain boundaries can hinder grain growth and dislocation migration, so that ODS steel can obtain good high-temperature mechanical properties, thereby obtaining the highest service temperature window. According to the information, the main methods for preparing ODS steel in the world currently include improved vacuum melting, mechanical alloying, sol-gel method and additive manufacturing.

[0003] The smelting method for preparing ODS steel has the advantages of short process flow, large single batch output, good batch-to-batch stability, and low manufacturing cost. However, there are also the following problems: 1. The solubility of rare earth elements in fully smelted steel is very low and forms segregation, resulting in a low rare earth content in the matrix that cannot form a sufficient amount of oxide dispersion phase. The method of strong stirring and rapid cooling can solve the above problems, but the obtained Y 2 O 3 The particle size is usually micron-sized, which cannot play a real role in dispersion strengthening; 2. The high reduction characteristics of rare earth atoms make it difficult for them to dissolve evenly with oxygen atoms in molten steel, and during the heating and melting process, the alloy will react with oxygen in the atmosphere to form oxides (such as W 2 O 3 、 2 O 5 , Fe 2 O 3 、SiO 2 and V 2 O 53. Rare earth oxides have very poor wettability with molten steel and are prone to aggregate and float, which eventually leads to insufficient rare earth oxides in the matrix. When the size is large or the morphology is irregular, it is easy to induce stress concentration or dislocation accumulation, reduce strength and toughness, and make the performance fail to meet the standards. In order to improve these problems, researchers have proposed various improved vacuum melting methods. Patent CN105274440A is to convert Fe 2 O 3 Directly placed in the ingot mold, the molten steel containing rare earth elements is poured in and Fe 2 O 3 The powder floats up and is mixed evenly. However, this method cannot control the rapid solidification of the ingot. After the oxygen-rich precursor is fully decomposed, it reacts with rare earth atoms to cause the rare earth oxide to precipitate with a size of more than 1 μm. The particle density is low and the matrix cannot be effectively strengthened. CN112481544A discloses a step-by-step smelting method for preparing ODS steel. First, an ingot containing oxygen carrier particles is smelted. Next, a molten steel containing rare earth elements is smelted and added to the ingot. The smelting process is controlled to dissolve part of the oxygen carrier particles. Finally, the ingot is obtained after cooling, and finally the ingot is rolled and heat-treated. This method greatly improves the distribution of oxide particles, but due to the smelting method used, there is still a problem of uneven dispersion.

[0004] The mechanical alloying method for preparing ODS steel is mainly to convert Y or Y 2 O 3 The raw materials are evenly dispersed into the matrix and mixed with the matrix elements at the atomic level. Then, the alloy powder is sintered into a block through a molding process such as hot isostatic pressing (HIP), and finally formed into a structural material by forging or extrusion. The outstanding advantage of this method is that it can realize the controllable composition of solid-state alloying under non-equilibrium thermodynamic conditions, and the grain size can be controlled by optimizing the heat treatment process. The process also has some disadvantages. First, the production cost is high and the production efficiency is low. The high-energy ball mill is loaded with less material, and multiple batches must be prepared to make a larger blank. The ball milling time is too long, resulting in low material preparation efficiency; secondly, the powder is easy to be contaminated and the process reproducibility is poor. The mechanical alloying powder has a large specific surface area, and it is easy to adsorb gas impurities. Even the loss of grinding balls entering the powder also causes pollution, making it difficult to ensure the quality stability of the material; finally, this method is limited by the size of the powder molding equipment and the hot processing equipment, and it is difficult to prepare large-size samples. In the CN102277525A patent, vacuum induction melting is used to prepare the master alloy and argon atomization is used to obtain the pre-alloyed powder, and then YH and nano Y are added 2 O 3High-energy ball milling is performed, and finally the bulk material is obtained by hot pressing sintering and hot isostatic pressing. Patent CN113477929 prepares materials by combining powder metallurgy and rolling. The difference is that the composition of the matrix alloy is screened by a method of learning. The other processes are similar. CN 116288031A mainly prepares ODS steel by mechanical alloying and hot extrusion. Y-Al-O, Y-Ti-O and Y-Zr-O type composite oxide dispersion phases are generated inside the material through component optimization and process control. The dispersion strengthening phase is small and dense: the average particle size is within 10nm, and the number density is ultra-high (>10 22 / m 3 ). CN104476842A patent discloses a layered toughened ODS steel and its preparation method, which mainly includes a matrix layer and a toughening layer alternately stacked with each other, wherein the matrix layer mainly includes a mother powder and Ti, Y 2 O 3 The toughening layer is mainly tantalum sheet. The main preparation method is to mechanically alloy the powder and then alternately stack it with Ta sheet, followed by spark plasma sintering. The thickness of the Ta sheet is 30μm, and the thickness of the matrix layer is 150-200μm.

[0005] The sol-gel method is a relatively new method that uses sol-gel, hydrogen reduction, mechanical alloying and powder sintering technology. This method mainly relies on the preparation process of nanomaterials. The ODS steel prepared in this way has excellent performance, uniform distribution of the dispersed phase and nanometer size. However, this method cannot achieve large-scale preparation, the impurity pollution introduced by the process itself cannot be ignored, and the process flow is very complicated (even mechanical alloying is one of the links), and the prospect of industrial production is not optimistic.

[0006] The continuous rise of additive manufacturing technology in recent years has provided a new way for the preparation of complex-shaped ODS steel components. However, laser additive manufacturing based on high-energy beam laser melting (including selective laser melting technology and direct energy deposition technology) is usually faced with unavoidable problems such as cracking, stress concentration and element segregation due to the rapid melting and solidification process. CN106868383B discloses a method for preparing nanostructured ODS steel workpieces using 3D printing technology. Selective laser melting technology is used to prepare ODS steel with nano-precipitated phase by adding a substrate with Zr element. CN116475427A discloses a photocuring printing process with low equipment cost, wide source of raw materials and easy to obtain, and has the potential for mass production.

[0007] In summary, various preparation methods have their advantages and disadvantages. It is urgent to provide a preparation method that can combine the advantages of the above methods to achieve rapid preparation of high-purity, solid-state alloying under non-equilibrium thermodynamic conditions, and controllable composition and grain of ODS steel, while avoiding the disadvantages of the above methods, which will surely provide an effective reference for large-scale production of ODS steel. Summary of the invention

[0008] The technical problems to be solved by the present invention are that the ODS steel prepared by the smelting method cannot play a real dispersion strengthening role, the oxide size is too large and difficult to remove, which will affect the performance of the ODS steel, and the rare earth oxides in the matrix are insufficient, resulting in the performance failing to meet the standards. The ODS steel prepared by the mechanical alloying method has high production cost, low production efficiency, and poor quality stability. The ODS steel prepared by the sol-gel method cannot achieve large-scale production, introduces a lot of impurities and pollution, and has a complicated process. The ODS steel manufactured by additive manufacturing is prone to cracking, stress concentration, and element segregation.

[0009] One of the purposes is to provide a method for preparing oxide dispersion strengthened steel, which solves the above-mentioned problems and realizes the rapid preparation of high-purity, solid-state alloyed ODS steel with controllable composition and controllable grains.

[0010] The second purpose is to provide an oxide dispersion strengthened steel prepared by the above method, which has the advantages of high purity, controllable alloying composition, controllable grains and stable quality.

[0011] The present invention is achieved through the following technical solutions:

[0012] In a first aspect, the present invention provides a method for preparing oxide dispersion strengthened steel, comprising the following steps:

[0013] S1. Processing low-activated ferrite martensite into strip-shaped steel;

[0014] S2, treating the surface of the annealed steel;

[0015] S3, stacking the surface treated steel and yttrium, vacuum sealing the stack with a sleeve, and then welding the sleeve;

[0016] S4, subjecting the welded jacket steel to hot isostatic pressing treatment;

[0017] S5. After hot isostatic pressing, the jacketed steel is hot rolled.

[0018] As a possible design, the above preparation method further includes step S6, repeating steps S1 to S5 3 to 10 times.

[0019] As a possible design, the low-activated ferrite martensite in the above step S1 is prepared by a smelting method; the steel material includes a steel strip and / or a steel plate, the thickness of the steel strip is 0.1mm to 0.5mm, and the thickness of the steel plate is 1mm to 3mm; the thickness of the yttrium foil is 0.01mm to 0.1mm.

[0020] As a possible design, the above step S1 also anneals the steel and puts the steel in an annealed state.

[0021] As a possible design, the surface treatment in the above step S2 is specifically to grind and clean the steel surface, then wipe it with ethanol and then blow it with nitrogen.

[0022] As a possible design, the steel and yttrium stacking in the above step S3 is specifically to treat the steel with yttrium source coating, and the thickness of the yttrium layer is 10nm to 200nm.

[0023] As a possible design, the stacking of steel and yttrium in the above step S3 is specifically to stack multiple layers of steel, with the yttrium foil being separated between two adjacent layers of steel.

[0024] As a possible design, the hot isostatic pressing in step S4 is specifically to diffusely connect the welded sheathed steel, heat it to 900°C to 1100°C, keep it at that temperature for 2h to 3h, cool it down, and then take it out of the furnace.

[0025] As a possible design, the above step S5 specifically includes heating the jacketed steel to 950° C. to 1100° C., performing heat preservation treatment, and rolling the jacketed steel to a thickness of 3 mm to 10 mm.

[0026] In a second aspect, the present invention also provides an oxide dispersion strengthened steel prepared by the above method.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] The preparation method of the present invention can completely avoid the floating of oxide powder during smelting; it is not troubled by the powder making problems in the mechanical and alloying processes, and organically combines the rapid and high-purity preparation advantages of the smelting method with the controllable composition and grain size advantages of mechanical alloying, and is expected to achieve mass production.

[0029] The present invention generates a dispersed strengthening phase in situ and realizes solid-state preparation of the material by a cumulative rolling method, and can regulate the grain size and the dispersed phase size at the same time. The O of the second phase particles generated in situ is obtained from the inside of the material.

[0030] The preparation method of the present invention can be applied to various ODS steels, has no restrictions on the types of the matrix and the dispersion strengthening phase of the material, and has a wide range of applications.

[0031] The present invention arranges yttrium between steel materials and combines the hot isostatic pressing process to help form defect-free diffusion connections between plates and between the plates and the sheath, greatly increasing the success rate of materials in the subsequent hot rolling process.

[0032] The present invention adopts a multiple accumulation rolling method, which can greatly improve the distribution of oxide particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0034] Figure 1 A schematic flow chart of a method for preparing oxide dispersion strengthened steel according to the present invention;

[0035] Figure 2 The room temperature tensile stress-strain curves of small samples of CLF steel after different times of rolling laps in Example 1 of the present invention;

[0036] Figure 3 This is the fracture morphology of the material after the third round of composite rolling in Example 1 of the present invention after room temperature stretching along the transverse direction (TD direction);

[0037] Figure 4 This is the phase diagram of the Fe-Y binary yttrium foil alloy of Example 6 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0039] A method for preparing oxide dispersion strengthened steel, referring to Figure 1 , including the following steps:

[0040] S1. Processing low activated ferrite martensite (RAFM steel) into strip-shaped steel.

[0041] In some embodiments of the present invention, the low-activated ferrite martensite in step S1 is prepared by a smelting method; the steel material includes a steel strip and / or a steel plate, the thickness of the steel strip is 0.1 mm to 0.5 mm, and the thickness of the steel plate is 1 mm to 3 mm.

[0042] In some embodiments of the present invention, the step S1 further includes annealing the steel.

[0043] Preferably, the above annealing conditions are 500-650°C for stress relief annealing and heat preservation for 1-3 hours. Annealing is stress relief annealing, which can eliminate a large number of dislocation structures and deformation structures inside the material, so that the material can restore its deformation ability and prepare for subsequent processes. Annealing is still required when repeating the same steps for the second time.

[0044] Preferably, the steel is further processed to obtain a suitable size.

[0045] S2. Surface treatment of the annealed steel.

[0046] In some embodiments of the present invention, the surface treatment in step S2 is specifically to grind and clean the steel surface, wipe it with ethanol, and then purge it with nitrogen.

[0047] Preferably, the grinding is performed by grinding the steel plate on a grinding machine or rough grinding the steel belt with sandpaper.

[0048] Preferably, the cleaning is ultrasonic cleaning with deionized water.

[0049] S3. Stack the surface treated steel and yttrium, vacuum seal them with a sheath, and then weld the sheath.

[0050] The steel and yttrium stacking can be performed by coating the steel with a yttrium source or by placing yttrium foil between the stacked steels.

[0051] Preferably, the number of stacking layers may be 10 to 500.

[0052] Preferably, the sheathing treatment in step S3 is to assemble the stacked steel and yttrium with a sheathing material (the sheathing material can be 304 stainless steel), introduce argon gas during welding, and perform an airtightness check on the sheath after welding to ensure that the sheath leakage rate is ≤10 -10 Pa·m 3 / s, and then the package is cold-exhausted to keep the vacuum degree below 1.0×10 -3 Pa, and finally the vacuum tube on the package was heated and clamped, and the vacuum degree was maintained at 1.0×10 -5 ~1.0×10 -2 Pa.

[0053] Preferably, the cold extraction exhaust time is 3h to 24h.

[0054] The exhaust has the following functions: one is to remove the air in the package to prevent oxidation of the Y foil or Y film, the other is to prevent leakage caused by gas expansion at high temperature, and finally to evenly transmit pressure.

[0055] Preferably, the vacuum pipe is clamped and sealed 2 to 6 times.

[0056] After the vacuum is drawn, the vacuum tube needs to be clamped and sealed to ensure that the inside of the package is a vacuum environment.

[0057] Preferably, after the steel and yttrium are stacked, a layer of Ti film is plated on the side for protection.

[0058] Solution 1: The steel and yttrium stacking in the above step S3 is specifically to treat the steel with yttrium source coating, and the thickness of the yttrium layer is 10nm to 200nm.

[0059] Preferably, the above coating method is PVD (physical vapor deposition) coating or ion sputtering coating.

[0060] Preferably, after the above-mentioned coating, a protective film of Ti or Cr is plated on the outer layer to prevent the film from being oxidized.

[0061] Preferably, when the steel is treated with yttrium source coating, when performing step S6, it is only necessary to stack the coated steel without repeating the coating of the steel.

[0062] Solution 2: The steel and yttrium stacking in the above step S3 is specifically to stack multiple layers of steel, with the yttrium foil separated between two adjacent layers of steel.

[0063] Preferably, the thickness of the yttrium foil is 0.01 mm to 0.1 mm.

[0064] Preferably, the yttrium foil is annealed before use and is in an annealed state before use. The yttrium foil is also processed to obtain a suitable size.

[0065] Preferably, the yttrium foil comprises a Y-containing binary alloy and / or a high-purity Y foil.

[0066] The above-mentioned Y binary alloy includes but is not limited to Y-Ti alloy and Zr-Y alloy.

[0067] S4. The welded sheath steel is subjected to hot isostatic pressing treatment.

[0068] In some embodiments of the present invention, the hot isostatic pressing in step S4 is specifically to diffusely connect the welded sheathed steel, heat it to 900°C to 1100°C, keep it at that temperature for 2h to 3h, cool it down, and then take it out of the furnace.

[0069] Preferably, the above diffusion bonding is carried out in a hot isostatic pressing furnace.

[0070] Preferably, the heating rate is 5°C / min to 10°C / min; after heating to 900°C, the pressure is 120MPa to 150MPa, and the temperature and pressure are kept for 2h to 3h, then cooled at a rate of 5°C / min to 7°C / min, and taken out of the furnace after the temperature is lower than 150°C.

[0071] After research, the inventors found that a heating rate that is too fast will cause a temperature difference between the inside and outside of the material, forming thermal stress, which is extremely unfavorable for material preparation, while a heating rate that is too slow will consume too much financial and time costs. Therefore, the heating rate is determined after comprehensive consideration.

[0072] The determination of the pressure size is closely related to the yield strength of the material at high temperature. If the pressure is too small, the material performance will be poor, and the sheath and material will not be able to deform at the corresponding temperature and cannot meet the requirements; if the pressure is too large, the sheath will easily rupture, so the pressure needs to be in the range of 120MPa to 150MPa.

[0073] If the cooling rate is too slow, the grain size inside the material will grow easily; if it is too fast, it will affect the grain size. It should be noted that it cannot be achieved too fast during the HIP process, and the cooling process will become slower and slower in the later stage.

[0074] Preferably, the hot isostatic pressing temperature range needs to be set in accordance with the corresponding alloy phase diagram, and the cooling rate needs to be controlled during the cooling process.

[0075] S5. After hot isostatic pressing, the jacketed steel is hot rolled.

[0076] In some embodiments of the present invention, the above step S5 specifically comprises heating the jacketed steel to 950° C. to 1100° C., subjecting the steel to heat preservation treatment, and rolling the steel to a thickness of 3 mm to 10 mm.

[0077] Preferably, the above step S5 is to place the jacketed steel in a box-type resistance furnace to heat it up.

[0078] Preferably, the jacketed steel is first heated to 830°C to 870°C at a rate of 5°C / min to 10°C / min, and then heated to 950°C to 1100°C at a rate of 5°C / min, and kept warm for 1h to 2h.

[0079] Heating at the above rate can avoid temperature differences inside and outside the material and reduce the formation of thermal stress.

[0080] Preferably, the temperature is raised to 850° C. at a rate of 5° C. / min to 10° C. / min.

[0081] Preferably, during the above rolling process, the pressing amount per pass is controlled at 0.5 mm to 5 mm, the final rolling temperature is controlled at 750° C. to 800° C., and after returning to the furnace, the steel is kept warm for 10 to 30 minutes and then hot rolled until the thickness reaches 3 mm to 10 mm.

[0082] The inventors have found that if the pressing amount is too large, the sleeve will crack, resulting in production failure; if the pressing amount is too small or insufficient, the steel strip layers cannot form diffusion connections, which also leads to failure and increases costs. Therefore, rolling within the above parameter range can ensure that diffusion connections are formed between the steel strip layers and ensure normal strengthening.

[0083] Preferably, the above rolling process needs to be repeatedly returned to the furnace for 3 to 10 times, and the pressing amount of each pass is gradually reduced.

[0084] The material is returned to the furnace to restore its deformation capacity. The pressure of each pass is gradually reduced because the material thickness becomes thinner and thinner as the rolling progresses. If the pressure is kept constant, the deformation of the material will become larger and larger, resulting in rupture of the sheath or breakage and delamination of the internal material.

[0085] S6. Repeat steps S1 to S5 3 to 10 times.

[0086] By repeatedly rolling for 3 to 10 times, uniform distribution of reinforcement can be achieved and material properties can be better.

[0087] In a second aspect, the present invention provides an oxide dispersion strengthened steel prepared by the above method.

[0088] Example 1

[0089] A method for preparing oxide dispersion strengthened steel comprises the following steps:

[0090] S1. Processing the low-activated ferrite martensite prepared by the smelting method into a strip of steel (the thickness of the steel strip is 0.1 mm), annealing the steel, and keeping the steel in the annealed state, and processing to obtain a suitable size;

[0091] S2. Clean the surface of the annealed steel with acetone or degreasing and rust removing agent to remove the oil stains on the surface, then polish the surface with sandpaper to expose the fresh surface, clean it with deionized water ultrasonically, wipe it with ethanol, and finally purge it with nitrogen;

[0092] S3. Stack the surface treated steel and yttrium in sequence and put them into the package. During welding, introduce argon gas. After welding, check the air tightness of the package to ensure that the leakage rate of the package is ≤10 -10 Pa·m 3 / s, then the package was cold-evacuated for 6 hours, and finally the exhaust pipe on the package was heated and clamped for 4 times, and the vacuum degree was kept below 1.0×10-3 Pa;

[0093] The stacking is specifically as follows: the steel is treated by yttrium source magnetron sputtering coating to obtain a double coating of Y and Ti with a thickness of 300 nm;

[0094] S4, diffusion-bonding the welded jacket steel, heating to 920°C at 5°C / min, and after heating to 900°C, keeping the temperature and pressure at 150MPa for 2h, and then cooling at a rate of 6°C / min, and taking out of the furnace when the temperature is lower than 150°C;

[0095] S5. After hot isostatic pressing, the jacketed steel is first heated to 850℃ at a rate of 5℃ / min, and then heated to 900℃ at a rate of 5℃ / min, and kept warm for 1h. During the rolling process, the pass pressure is controlled at 1mm~2mm, and the final rolling temperature is controlled at 750℃. After returning to the furnace (returning to the furnace for 5 times), it is kept warm for 10min and hot rolled until the thickness is 2mm. After each return to the furnace, observe the material damage, such as Figure 2 As shown;

[0096] S6, repeat steps S1 to S5 3 times, Figure 3 This is the fracture morphology of the material after room temperature tensile stretching along the transverse direction (TD direction) after the third round of composite lamination. After each repetition, the tensile stress and strain of the rolled material are recorded. The results are shown in Figure 2 shown.

[0097] Table 1 shows the attached Figure 3 Point scanning energy spectrum results of the corresponding points in .

[0098] Table 1 Attachment Figure 3 Point scanning spectrum results of the corresponding points in

[0099]

[0100] Figure 2 In the figure, 1st-CLF-RD is the First rolling-RD in the curve, specifically the tensile stress-strain curve of the CLF steel substrate after one rolling along the RD direction; 2nd-CLF-RD is the Second rolling-RD in the curve, specifically the tensile stress-strain curve of the CLF steel substrate after two rolling along the RD direction; 3rd-CLF-RD is the Third rolling-RD in the curve, specifically the tensile stress-strain curve of the CLF steel substrate after three rolling along the RD direction; the difference between 3rd-CLF-TD and 3rd-CLF-RD is that the CLF steel substrate is rolled along the TD direction. Among them, TD is the transverse direction, which refers to the direction perpendicular to the rolling direction; RD is the rolling direction, which refers to the moving direction of the metal when rolling the product.

[0101] from Figure 2 It can be seen that with the increase in the number of hot rolling times, the tensile strength of the material first decreases and then increases. The strength of the material is the highest after the third hot rolling. The room temperature tensile strength of the CLF steel substrate is about 650MP, and the matrix material is greatly strengthened.

[0102] Example 2

[0103] A method for preparing oxide dispersion strengthened steel comprises the following steps:

[0104] S1. Processing low-activated ferrite martensite prepared by a smelting method into a strip of steel (the thickness of the steel plate is 1 mm), annealing the steel, and keeping the steel in an annealed state to obtain a suitable size;

[0105] S2. Clean the surface of the annealed steel with acetone or degreasing and rust removing agent to remove the oil stains on the surface, then polish the surface with sandpaper to expose the fresh surface, clean it with deionized water ultrasonically, wipe it with ethanol, and finally purge it with nitrogen;

[0106] S3. Stack the surface treated steel and yttrium, stack the steel plates and Zr foils alternately and put them into the package. During welding, introduce argon gas. After welding, check the air tightness of the package to ensure that the leakage rate of the package is ≤10 -10 Pa·m 3 / s, then the package was cold-evacuated for 12 hours, and finally the exhaust pipe on the package was heated and clamped for 3 times, and the vacuum degree was maintained at 1.0×10 -5 ~1.0×10 -2 Pa;

[0107] The stacking is specifically as follows: the surface of the Zr foil is polished with sandpaper to expose the fresh surface, the surface is ultrasonically cleaned with deionized water, wiped with ethanol and finally purged with nitrogen, and then annealed and kept in an annealed state before use, processed into a suitable size, and then multiple layers of steel are stacked, with the yttrium foil separated between two adjacent layers of steel, and the thickness of the yttrium foil is 0.1 mm;

[0108] S4, diffusion-bonding the welded jacket steel, heating to 920°C at 5°C / min, and after heating to 900°C, keeping the temperature and pressure at 150MPa for 2h, and then cooling at a rate of 6°C / min, and taking out of the furnace when the temperature is lower than 150°C;

[0109] S5. After hot isostatic pressing, the jacketed steel is first heated to 850°C at a rate of 5°C / min, and then heated to 900°C at a rate of 5°C / min, and kept warm for 1h. During the rolling process, the pass pressing amount is controlled at 1mm-2mm, and the final rolling temperature is controlled at 750°C. After returning to the furnace (returning to the furnace 5 times), it is kept warm for 10min and hot rolling is continued until the thickness is 2mm;

[0110] S6. Repeat steps S1 to S5 7 times.

[0111] Example 3

[0112] A method for preparing oxide dispersion strengthened steel comprises the following steps:

[0113] S1. Processing the low-activated ferrite martensite prepared by the smelting method into a strip of steel (the thickness of the steel strip is 0.1 mm), annealing the steel, and keeping the steel in the annealed state, and processing to obtain a suitable size;

[0114] S2. Clean the surface of the annealed steel with acetone or degreasing and rust removing agent to remove the oil stains on the surface, then polish the surface with sandpaper to expose the fresh surface, clean it with deionized water ultrasonically, wipe it with ethanol, and finally purge it with nitrogen;

[0115] S3. Stack the surface treated steel and yttrium, assemble them with sheath materials, introduce argon gas during welding, and check the sheath for air tightness after welding to ensure that the sheath leakage rate is ≤10 -10 Pa·m 3 / s, and then the package was cold-exhausted for 24 hours, and the vacuum degree was kept below 1.0×10 -3 Pa, and finally the vacuum tube on the package was heated and clamped for 6 times, and the vacuum degree was maintained at 1.0×10 -5 ~1.0×10 -2 Pa;

[0116] The above stacking is specifically:

[0117] Yttrium foil (Ti-Y alloy ingot processed into 0.05 mm thick foil) is annealed and kept in an annealed state before use, processed into a suitable size, and then multiple layers of steel are stacked, with the yttrium foil separated between two adjacent layers of steel;

[0118] S4, diffusion-bonding the welded jacket steel, heating to 900°C at 5°C / min, and then keeping the temperature and pressure at 150MPa for 2h, and then cooling at a rate of 6°C / min, and taking out of the furnace when the temperature is lower than 150°C;

[0119] S5. After hot isostatic pressing, the jacketed steel is first heated to 870°C at a rate of 5°C / min, and then heated to 950°C at a rate of 5°C / min, and kept warm for 1h. During the rolling process, the pass pressing amount is controlled at 1mm-2mm, and the final rolling temperature is controlled at 750°C. After returning to the furnace (returning to the furnace 10 times), it is kept warm for 10min and hot rolling is continued until the thickness is 2mm;

[0120] S6. Repeat steps S1 to S5 7 times.

[0121] Example 4

[0122] A method for preparing oxide dispersion strengthened steel comprises the following steps:

[0123] S1. Processing 304 stainless steel prepared by a smelting method into a strip of steel (the thickness of the steel strip is 0.1 mm), annealing the steel, and keeping the steel in an annealed state, and processing to obtain a suitable size;

[0124] S2. Clean the surface of the annealed steel with acetone or degreasing and rust removing agent to remove the oil stains on the surface, then polish the surface with sandpaper to expose the fresh surface, clean it with deionized water ultrasonically, wipe it with ethanol, and finally purge it with nitrogen;

[0125] S3. Stack the surface treated steel and yttrium, assemble them with sheath materials, introduce argon gas during welding, and check the sheath for air tightness after welding to ensure that the sheath leakage rate is ≤10 -10 Pa·m 3 / s, and then the package was cold-exhausted for 24 hours, and the vacuum degree was kept below 1.0×10 -3 Pa, and finally the vacuum tube on the package was heated and clamped for 6 times, and the vacuum degree was maintained at 1.0×10 -5 ~1.0×10 -2 Pa;

[0126] The stacking is specifically as follows: yttrium foil (high purity Y foil) is annealed and in an annealed state before use, processed into a suitable size, and then multiple layers of steel are stacked, with the yttrium foil separated between two adjacent layers of steel, and the thickness of the yttrium foil is 0.1 mm;

[0127] S4. Diffusion-bond the welded jacket steel, heat it to 920°C at a rate of 10°C / min, and after heating to 900°C, keep it at a pressure of 150MPa for 3h, and then cool it at a rate of 5°C / min, and take it out of the furnace when the temperature is lower than 150°C;

[0128] S5. After hot isostatic pressing, the jacketed steel is first heated to 850°C at a rate of 5°C / min, and then heated to 900°C at a rate of 5°C / min, and kept warm for 2h. During the rolling process, the pass pressing amount is controlled at 1mm-2mm, and the final rolling temperature is controlled at 800°C. After returning to the furnace (returning to the furnace 10 times), it is kept warm for 30min and hot rolling is continued until the thickness is 2mm;

[0129] S6. Repeat steps S1 to S5 three times.

[0130] Example 5

[0131] A method for preparing oxide dispersion strengthened steel comprises the following steps:

[0132] S1. Processing the FeCrAl steel prepared by the smelting method into a strip-shaped steel material (the thickness of the steel plate is 1 mm), annealing the steel material, and keeping the steel material in the annealed state, and processing it to obtain a suitable size;

[0133] S2. Clean the surface of the annealed steel with acetone or degreasing and rust removing agent to remove the oil stains on the surface, then polish the surface with sandpaper to expose the fresh surface, clean it with deionized water ultrasonically, wipe it with ethanol, and finally purge it with nitrogen;

[0134] S3. Stack the surface treated steel and yttrium, assemble them with sheath materials, introduce argon gas during welding, and check the sheath for air tightness after welding to ensure that the sheath leakage rate is ≤10 -10 Pa·m 3 / s, and then the package was cold-exhausted for 24 hours, and the vacuum degree was kept below 1.0×10 -3 Pa, and finally the vacuum tube on the package was heated and clamped for 5 times, and the vacuum degree was maintained at 1.0×10 -5 ~1.0×10 -2 Pa;

[0135] The stacking is specifically as follows: yttrium foil (high purity Y foil) is annealed and in an annealed state before use, processed into a suitable size, and then multiple layers of steel are stacked, with the yttrium foil separated between two adjacent layers of steel, and the thickness of the yttrium foil is 0.1 mm;

[0136] S4, diffusion-bonding the welded jacket steel, heating to 1000°C at 8°C / min, and after heating to 900°C, keeping the temperature and pressure at 120MPa for 3h, and then cooling at a rate of 7°C / min, and taking out of the furnace when the temperature is lower than 150°C;

[0137] S5. After hot isostatic pressing, the jacketed steel is first heated to 830°C at a rate of 7°C / min, and then heated to 1100°C at a rate of 5°C / min, and kept warm for 2h. During the rolling process, the pass pressing amount is controlled at 1mm-2mm, and the final rolling temperature is controlled at 800°C. After returning to the furnace (returning to the furnace 10 times), it is kept warm for 20min and hot rolling is continued until the thickness is 2mm-4mm;

[0138] S6. Repeat steps S1 to S5 4 times.

[0139] Example 6

[0140] A method for preparing oxide dispersion strengthened steel comprises the following steps:

[0141] S1. Processing the Q235R steel prepared by the smelting method into a strip-shaped steel material (the thickness of the steel strip is 0.1 mm), annealing the steel material, and keeping the steel material in the annealed state, and processing to obtain a suitable size;

[0142] S2. Clean the surface of the annealed steel with acetone or degreasing and rust removing agent to remove the oil stains on the surface, then polish the surface with sandpaper to expose the fresh surface, clean it with deionized water ultrasonically, wipe it with ethanol, and finally purge it with nitrogen;

[0143] S3. Stack the surface treated steel and yttrium, assemble them with sheath materials, introduce argon gas during welding, and check the sheath for air tightness after welding to ensure that the sheath leakage rate is ≤10 -10 Pa·m 3 / s, and then the package was cold-exhausted for 24 hours, and the vacuum degree was kept below 1.0×10 -3 Pa, and finally the vacuum tube on the package was heated and clamped for 6 times, and the vacuum degree was maintained at 1.0×10 -5 ~1.0×10 -2 Pa;

[0144] The stacking is specifically: Yttrium foil (Fe-Y alloy ingot is processed into a foil with a thickness of 0.1 mm, referring to Figure 4 ) is annealed and in an annealed state before use, processed into a suitable size, and then multiple layers of steel are stacked, with yttrium foil separated between two adjacent layers of steel;

[0145] S4. Diffusion-bond the welded jacket steel, heat it to 1100°C at 10°C / min, and after heating to 900°C, keep it at 150MPa for 2.5h, and then cool it at a rate of 7°C / min, and take it out of the furnace when the temperature is lower than 150°C;

[0146] S5. After hot isostatic pressing, the jacketed steel is first heated to 870°C at a rate of 10°C / min, and then heated to 1100°C at a rate of 5°C / min, and kept warm for 2h. During the rolling process, the pass pressing amount is controlled at 1mm-2mm, and the final rolling temperature is controlled at 800°C. After returning to the furnace (returning to the furnace 10 times), it is kept warm for 60min and hot rolling is continued until the thickness is 2mm-4mm;

[0147] S6. Repeat steps S1 to S5 5 times.

[0148] observe Figure 4 , Figure 4 The figure shows the Fe-Y binary alloy phase diagram. It can be seen from the figure that the lowest liquidus temperature is 1173K, that is, 900℃. Therefore, in order to avoid eutectic melting between CLF steel and Y foil during hot isostatic pressing, the hot isostatic pressing sintering temperature cannot be higher than 900℃.

[0149] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing oxide dispersion strengthened steel, characterized in that: The steps include: S1. Processing low-activated ferrite martensite into strip-shaped steel; S2, treating the surface of the annealed steel; S3, stacking the surface treated steel and yttrium, vacuum sealing the stack with a sleeve, and then welding the sleeve; S4, subjecting the welded jacket steel to hot isostatic pressing treatment; S5. After hot isostatic pressing, the jacketed steel is hot rolled.

2. The method for preparing oxide dispersion strengthened steel according to claim 1, characterized in that: The method further comprises step S6, repeating steps S1 to S5 3 to 10 times.

3. The method for preparing oxide dispersion strengthened steel according to claim 1, characterized in that: The low-activated ferrite martensite in step S1 is prepared by a smelting method; the steel material includes a steel strip and / or a steel plate, the thickness of the steel strip is 0.1 mm to 0.5 mm, and the thickness of the steel plate is 1 mm to 3 mm.

4. The method for preparing oxide dispersion strengthened steel according to claim 1, characterized in that: The step S1 also anneals the steel material and puts the steel material into an annealed state.

5. The method for preparing oxide dispersion strengthened steel according to claim 1, characterized in that: The surface treatment in step S2 specifically comprises grinding and then cleaning the steel surface, wiping it with ethanol, and then purging it with nitrogen.

6. The method for preparing oxide dispersion strengthened steel according to claim 2, characterized in that: The steel and yttrium stacking in step S3 specifically involves treating the steel with yttrium source coating, and the thickness of the yttrium layer is 10nm to 200nm.

7. The method for preparing oxide dispersion strengthened steel according to claim 2, characterized in that: The steel and yttrium stacking in step S3 specifically involves stacking multiple layers of steel, with the yttrium foil being separated between two adjacent layers of steel.

8. The method for preparing oxide dispersion strengthened steel according to claim 1, characterized in that: The hot isostatic pressing in step S4 specifically involves diffusion bonding the welded sheathed steel, heating it to 900° C. to 1100° C., keeping it at that temperature for 2 h to 3 h, cooling it down, and then taking it out of the furnace.

9. The method for preparing oxide dispersion strengthened steel according to claim 1, characterized in that: The step S5 specifically includes heating the jacketed steel to 950° C. to 1100° C., performing heat preservation treatment, and rolling the jacketed steel to a thickness of 3 mm to 10 mm.

10. An oxide dispersion strengthened steel, characterized in that: The steel is prepared using the method for preparing oxide dispersion strengthened steel as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of oxide dispersion strengthened stainless steel powder and stainless steel

    CN102277525A

  • Laminar toughened ODS steel and preparation method thereof

    CN104476842A

  • Oxide dispersion strengthened (ODS) steel preparing method and martensitic steel

    CN105274440A

  • Method for preparing nanostructured oxide dispersion-reinforced steel workpieces using 3D printing technology

    CN106868383B

  • Preparation method of high-density oxide dispersion strengthened steel

    CN112481544A